Do Engagement Quality Reviewers’ Workplace Ties with Engagement Partners Influence Audit Quality? - Qi, Yue; Seidel, Timothy A.; Zhang, Joseph H.; Zhang, Junsheng (Journal of Accounting Research, 2026)
ABSTRACT The engagement quality review is a key component of an audit firm's quality control system. This study leverages unique data on individual engagement quality reviewers (EQRs) to examine how previous shared working experience between EQRs and engagement partners affects audit quality. While prior research suggests that within‐firm network ties between predecessor and successor partners facilitate knowledge transfer, we find that prior shared working experience between EQRs and engagement partners is associated with lower audit quality. Mechanism tests indicate that such experience is associated with a higher likelihood of regulatory enforcement actions related to deficiencies in audit procedures, insufficient evidence, and a lack of professional skepticism. We also find that such experience corresponds with higher materiality thresholds, suggesting reduced scrutiny during audit planning and execution. Additional analyses reveal that these adverse effects primarily arise when previous shared working relationships did not produce adverse outcomes, when EQRs are not audit industry leaders, and when they face lower reputational risk. These findings are especially salient given that EQRs’ previous shared working experience with engagement partners appears to weigh heavily in EQR assignments. Overall, our study provides important insights into the implications of EQR independence and the determinants of engagement quality review effectiveness.